Sengketa Tanah pada Masyarakat Adat di Depapre : Studi Kasus Klan Tonggrotuw dan Soumilena - Sario Itlay (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2020)
This research examines the land conflict that occurred in Depapre, Papua, involving indigenous communities and the local government regarding the construction of a container port. This conflict occurs due to claims of dual ownership of land as well as differences in understanding regarding customary law and national law. Indigenous people consider this land as their ancestral heritage, while the government claims it as state land. The conflict is exacerbated by the absence of an agreement that is considered fair by the community, as well as unclear boundaries of the land used for the project. A qualitative approach with a case study method is used to explore the causes of conflict and efforts to resolve it. The research results show that land conflicts in Depapre are the result of weak social structures and low understanding of customary law and national law. This research emphasizes the importance of cooperation between indigenous peoples and the government to resolve land conflicts fairly and prevent similar conflicts in the future